(untitled) (Journal of the College of Basic Education, 2022)
The critical academic and non-academic critiques of the poetry of the sixties were based on different methodologies. The interest in these methodologies was a field of critical studies produced by the poets of the sixties. Many criticisms appeared in poets, And these proposals are subjective and reflect the crystallization of their ideas and the construction of their personalities, or addressed to the generation of the French generation in general, and the tendencies of critics and their trends as they engage in their experiences of cash, every critic or critical study goal seeks to justify and interpret Which invited some critics to repeat many questions about the acceptance of the experience of the sixtieth, and the rush of some critical views towards it, and the admiration of the poet in the status of his poetry. We have found that it is easy to identify these methodologies. However, it is worth noting that most of these studies rarely relied on one approach that is easy to determine in their applied critique of this poetry, combining practical measures from different approaches. This phenomenon has been found in quite a few critics who have been keen to rid the practice of cash from the one-track method to consecrate the complementary efforts they were seeking. The reality of Iraqi criticism in the sixties and the following was relatively stable and conservative, and most critics followed the realistic approach in all its forms in line with the scene of life: politically, socially, and culturally. Traditional monetary experiences seemed to be far from modern experiences, which were later largely based on impression and influence. The critical discourse appeared to be confined to a practice that only knew the contextual monetary perspectives. The textual procedure was not historically achieved in Arab monetary practices until the second half of the 20th century and in the mid-1960s. The critics of the texts of the poetry of the sixties, and dealt with the critical lesson, taking from the contextual approaches to them. Critics have resorted to this kind of critical approach in the belief that the poetic experience, despite its complexity and precision, has its own impact in the context, including images and inspirations, interpreting poetry texts historically, socially, politically, and psychologically. The presence of a clear analysis of these approaches, especially the psychological approach. The linkage of the poetic texts with contextual data seemed inevitable in critical discourse, especially as this generation grew up in a time of serious cultural and intellectual transformations. This is closer to the impressionist criticism of the author’s personality and the age of authorship, the interpretation of certain statements related to politics and self-assembly, The critic draws evidence to reinforce his ideological or social vision in which the outside world shows the text and does not raise the main problems that are at the heart of the text but rather are based on an ideological pattern. Most of them were based on contextual analysis, especially historical or sociological, as the contextual critics did not refer to the theory until late in the mid-1980s. The 1970s and 1980s Were the important incubator for the emergence of systematic criticism, which has become dominated by a set of methodologies controlling in control away from the subjective and impression. Letters of cash remained almost as stable until the winds of change mixed with modernity, and modern criticism emerged. Critical analysis has undergone serious transformations in its adopted methods. This change was homogeneous to the change in the poetic movement. These old methods no longer absorb what is new in the poetic text. There were many critics whose speeches varied and varied. The modern monetary project was an indirect call to free the monetary work from a monolithic approach, and to reconcile the multiple approaches. Despite their multiplicity of monetary methodologies and their differences, these methodologies witnessed a cash surge fueled by multiple factors. (The text - language - style) material for them in their monetary curricula and continued movement of monetary modernization, the second feature appeared in the stage of post-modern methodologies where the Subsequent to the structural, from stylistic and Semiotics, and received and the dismantling. The new criticism has made its way into the textual and linguistic examination of the poetic discourse, revealing its expressive and stylistic themes and exploiting textual and semantic data